2007
DOI: 10.1039/b618668h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and preliminary DNA-binding studies of diimineplatinum(ii) complexes containing 3- or 4-pyridineboronic acid

Abstract: A series of platinum(II) complexes of the type [Pt(NN)(pyB) 2 ](NO 3 ) 2 (NN = bipy, phen; pyB = 3-or 4-pyridineboronic acid) were successfully prepared and fully characterised by 1D-and 2D-multinuclear NMR spectroscopy and ESI-MS. Using VT 1 H NMR spectroscopy, rotational isomers for [Pt(NN)(3-pyB) 2 ](NO 3 ) 2 were identified and the free energies of activation for rotation of 3-pyB about the Pt-N bond were determined to be DG ‡ 310 = 69.2 ± 0.1 kJ mol −1 and DG ‡ 305 = 66.0 ± 0.1 kJ mol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…These results were interpreted by the conformation of the rings seen in the X-ray crystal structure of [Pt(py) 2 (AtC2)](NO 3 ) 2 . The structures of platinum complexes containing pyridine have been investigated by many workers (Ching et al, 2007;Cavigliasso et al, 2013) and, in many cases, the two pyridine rings show a symmetrical orientation. However, in (I), the N3-Pt1-N1-C1 torsion angle is 110.2 (2) , whereas that of N4-Pt1-N2-C10 is À60.1 (3) , indicating an asymmetrical orientation (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…These results were interpreted by the conformation of the rings seen in the X-ray crystal structure of [Pt(py) 2 (AtC2)](NO 3 ) 2 . The structures of platinum complexes containing pyridine have been investigated by many workers (Ching et al, 2007;Cavigliasso et al, 2013) and, in many cases, the two pyridine rings show a symmetrical orientation. However, in (I), the N3-Pt1-N1-C1 torsion angle is 110.2 (2) , whereas that of N4-Pt1-N2-C10 is À60.1 (3) , indicating an asymmetrical orientation (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the speciation of free 3-and 4-pyB and their platinum(II)-diimine complexes is highly pH dependent. 26,12 The resonances assigned to the pyB protons, H2¢¢¢ and H3¢¢¢ (for 4-pyB) and H2¢¢¢ (for 3-pyB), were found to shift substantially as a function of pH. At pH > 5, hydroxylation of the boronic acid functionality occurs to afford the tetrahedral boronate species, and at this pH…”
Section: Synthesis and Variable Ph Measurementsmentioning
confidence: 99%
“…195 Pt{ 1 H} NMR spectroscopy was used to confirm the coordination environment of 1•2NO 3 , 2•2NO 3 , and 3•3NO 3 : the presence of single resonances at -2752, -2750, and -2660 ppm, respectively, is consistent with a PtN 4 core in each complex. 23,12 In contrast, a PtN 3 S coordination geometry. 24, 25 The results of 11 B{ 1 H} NMR spectroscopy confirmed the presence of the boronic acid group with a singlet observed at ca.…”
Section: Synthesis and Variable Ph Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our group has shown that ligands containing the thermodynamically stable 1,12-carborane cluster do not degrade upon complexation to gold(I) (Ioppolo et al, 2007a,b). Boron-containing ligands and their respective complexes are of interest for potential application in boron neutron capture therapy (BNCT) (Crossley et al, 2005(Crossley et al, , 2007Todd et al, 2005;Ioppolo et al, 2007a,b;Ching et al, 2007). For the synthesis of the precursor gold compound, see: Uson et al (1989).…”
Section: Related Literaturementioning
confidence: 99%